2018
DOI: 10.5539/jas.v11n1p81
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Improvement of Grain Quality Promoted by High and New Technology in Rice

Abstract: Rice (Oryza sativa L.) is considered as one of the most important food crops all over the world. Because of the improvement of the actual living standards, there is more and more demand for improved grain quality. Although, the grain quality is a very complex quantitative trait in rice, it has great scientific significance and practical application value for the improvement of the quality of rice grain using high and up to date techniques. Here, we focus on the new advances in the application of the genetic im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…DNA targeted endonuclease technology can repair damaged DNA by homologous recombination or non homologous terminal connection by breaking double strands of DNA at the target site of genome, so as to achieve targeted knockout, knockin and gene modification of target site (Peng et al, 2019). The immune memory of CRISPR/Cas system is stored in the form of foreign genome interval sequence inserted into CRISPR array (Koonin et al, 2017).…”
Section: Crispr/cas9 Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…DNA targeted endonuclease technology can repair damaged DNA by homologous recombination or non homologous terminal connection by breaking double strands of DNA at the target site of genome, so as to achieve targeted knockout, knockin and gene modification of target site (Peng et al, 2019). The immune memory of CRISPR/Cas system is stored in the form of foreign genome interval sequence inserted into CRISPR array (Koonin et al, 2017).…”
Section: Crispr/cas9 Technologymentioning
confidence: 99%
“…It is urgent to further improve the yield of rice to ensure global food security (He, 2014). In recent decades, with the continuous improvement of people's living standards, the demand for high-quality rice is also increasing (Peng et al, 2019). Therefore, increasing rice yield and improving rice quality are the focus of attention of rice breeders and botanists.…”
Section: Introductionmentioning
confidence: 99%
“…The cultivated species are Oryza sativa (Asian rice), grown worldwide, and the second species is Oryza glaberrima (African rice), cultivated on a limited scale in the west. Rice comes in second after wheat in its nutritional content, as it is rich in high-energy sources such as carbohydrates and proteins [1,2]. The rice crop has different morphological and physiological IOP Publishing doi:10.1088/1755-1315/1262/5/052039 2 characteristics from other grains, where the stomata are large, the skin of its leaves is very thin, and it is relatively resistant to water loss, its carbon metabolism rate is lower, and the water use efficiency is lower.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that through CRISPR/Cas9-mediated genome editing, the probability of obtaining homozygous or biallelic genes is as high as 90% in T 0 generation [ 24 ]. Previous studies suggest that mutations in the GS3 gene results in increased GL and GWT, and the overall yield improvement [ 25 ]. Zhao et al (2018) [ 16 ] used CRISPR/Cas9 technology to generate mutations in the first exon of GS9 , which resulted in a frameshift mutation, disrupted GS9 normal expression, and increased GL.…”
Section: Introductionmentioning
confidence: 99%